Flow field around the front wings of formula-1 racing car model : BAR Honda 003 and MP4-21 - Lau, Chia Sheng. (2009)
The author reviewed the progress and evolution for the past 100 years of automotive racing, in particular the front wing of an open-wheel race cars. In today’s Formula One Racing, the front wing of a Formula One Race Car is crucial in generating downforce, contributing to about one third of the total downforce generated. A few types of front wings were being introduced throughout the years of evolution. Two of them were the straight wing and the curved (U-shaped) wing. The difference in performance and flow structures between the two types of wings were being experimentally investigated by the author using scaled models. Advanced experimental method such as Laser Particle Image Velocimetry was used for better understanding of the flow structure. On top of that, the author looked into the actual scaled wing model on track condition with moving ground effect. This was done using computational modeling with the effect of ground clearance on the generation of downforce and drag for both wings being studied. In general, the straight wing performs better than the curved wing with larger downforce generation. However, this larger downforce comes with a greater penalty in drag. An ideal balance point between downforce and drag is being sought by modern race car designers.